084 Neurological presentations of rare chloromas in the context of haematological malignancy. (23rd August 2021) - Chatterton, Sophie; Helou, Jacob; Drummond, James; Ward, Christopher; Coyle, Luke; Ng, Karl
Abstract : Objective(s): To describe the spectrum of neurological presentations of chloromas. Method: Two case reports. Results: A 72 year-old female presented with a right-sided cavernous sinus syndrome on a background of a myeloproliferative disorder. MRI brain demonstrated a FLAIR hyperintense lesion centred on the right cavernous sinus. Cerebrospinal fluid (CSF) was acellular with negative cytology and flow cytometry. FDG PET/CT demonstrated diffuse marrow hypermetabolism, hepatosplenomegaly and focal FDG uptake in the cavernous sinus and a remote paraspinal region, suspicious for chloromas. The patient developed pancytopaenia with blasts, and tumour lysis syndrome (TLS) consistent with transformation to acute myeloid leukaemia (AML). The patient was given pulse methylprednisolone, hydroxyurea and external beam radiotherapy to the cavernous sinus lesion with symptomatic improvement. The second case is of a 76 year-old male who presented with progressive lower limb weakness with acute faecal incontinence. This was on a background of AML treated with induction STIMULus (cytarabine and thioguanine) followed by remission confirmed on a recent bone marrow biopsy. CSF showed a marked lymphocytosis with many undifferentiated cells, and flow cytometry was consistent with AML. An MRI whole spine demonstrated a solitary avidly enhancing intramedullary T11 cord lesion with associated oedema. In the context of AML and CSF pathology this was thought to reflect an intramedullary chloroma. The patient was treated with external beam radiotherapy, pulse intravenous methylprednisolone and intrathecal chemotherapy with symptomatic improvement. Conclusion: These two cases demonstrate the diversity of neurological clinical presentations of chloromas, an unusual collection of leukaemic cells exerting mass-like effect.